2017
DOI: 10.1007/s11912-017-0624-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Stratification of Patients With Advanced Oral Cavity Squamous Cell Carcinoma

Abstract: In addition to several pathologic factors that have been proposed to improve prognostic stratification and treatment planning in the eighth edition of the American Joint Committee staging manual on cancer, we reviewed some other imaging and clinicopathological parameters demonstrated to be closely associated with patient prognosis, along with the biomarkers related to novel target or immune therapy. Evaluation of current literature regarding the prognostic stratification used in contemporary clinicopathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 89 publications
0
20
0
Order By: Relevance
“…An elevated score is a risk factor for long-term outcomes and is associated with high overall stage, ENE, perineural invasion, and tumor depth. According to our previous studies, ENE, cell differentiation, and perineural invasion have been demonstrated as important prognostic factors 2527 . Consequently, the ANS, incorporated with TNM stage, age, sex, ENE, cell differentiation, and perineural invasion, was constructed as this prognostic nomogram to predict OS.…”
Section: Discussionmentioning
confidence: 92%
“…An elevated score is a risk factor for long-term outcomes and is associated with high overall stage, ENE, perineural invasion, and tumor depth. According to our previous studies, ENE, cell differentiation, and perineural invasion have been demonstrated as important prognostic factors 2527 . Consequently, the ANS, incorporated with TNM stage, age, sex, ENE, cell differentiation, and perineural invasion, was constructed as this prognostic nomogram to predict OS.…”
Section: Discussionmentioning
confidence: 92%
“…Oral cavity squamous cell carcinoma (OSCC) is one of the most common malignant diseases, accounting for more than 10,000 deaths every year and approximately 3% of all cancer cases estimated annually worldwide . Although there have been improvements in therapeutic approaches, the 5‐year overall survival rate of patients with OSCC remains at approximately 50% . Environmental risk factors, including cigarette smoking, alcohol consumption, and betel quid chewing, contribute to the development and progression of OSCC by facilitating genetic changes, genomic aberrations, and widespread genomic instability .…”
Section: Introductionmentioning
confidence: 99%
“…The contemporary treatment is mainly based on tumor staging and include surgery and adjuvant therapies, such as chemotherapy and radiotherapy. Although the improvement of the current diagnostic and therapeutic strategies, the 5‐year overall survival rate has still been approximately 60% for last few decades . In order to improve the detection and/or treatment of OSCC, the discovery of OSCC‐associated biomarkers may increase our understanding of the OSCC tumorigenesis and disclose the associated molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances in treatment, OSCC is still associated with significant morbidity and mortality. In Taiwan, OSCC is the commonest malignancy in males between 30 and 50 years of age and its incidence has also increased over the last three decades (De Paz, Kao, Huang, & Chang, 2017; Hsu, Yu, Chiang, Chen, & Wang, 2017). Similarly, diabetes mellitus (DM) is a leading cause of mortality globally and the World Health Organization estimates it to be the seventh leading cause of mortality in 2016.…”
Section: Introductionmentioning
confidence: 99%